The Role of Corporate Governance Attributes in Moderating the Impact of Dividend Policy on Firm Value: Evidence from the Indonesian Manufacturing Sector - Hamzah Gymnastiar; Hasan Mukhibad; Noor Ismawati Jafar (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
To date, empirical findings on the relationship between dividend policy and firm value remain inconsistent, particularly in emerging markets with relatively weak governance quality and investor protection. Unlike other studies that only examine the direct effects, this study includes several indicators of good corporate governance (GCG), namely the proportion of independent commissioners, board meeting frequency, board busyness, and board size, as moderating variables. Panel data regression was performed to analyze a sample of 45 manufacturing companies in the primary consumer goods sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The results indicate that dividend policy has no significant direct impact on firm value. However, board independence and board size magnify the effect of dividend policy on firm value, while board busyness weakens it. Board meeting frequency, on the other hand, exerts no effect on this relationship. These findings suggest that the effectiveness of dividend policy depends on the quality of governance. This study provides new evidence from Indonesia and has practical implications for companies and regulators seeking to improve the credibility of governance in dividend policy decision-making.